Analisis Unsur Gharar dalam Transaksi Saham Syariah: Antara Spekulasi dan Kepatuhan Etika Pasar Modal Syariah di Indonesia - Taufik Darmawansyah, Trisna; Anwar, Rosihon; Najib, Moh; Harya pradyanegara, Arkananta; Aguspriyani, Yani (Program Studi Manajemen Keuangan Syariah, 2026)
The Islamic capital market in Indonesia faces challenges due to speculative practices containing elements of Gharar (uncertainty), which contradict the principles of Islamic law. This reduces market stability and undermines public confidence in the Islamic financial system. This study aims to analyze the influence of Gharar in Sharia-compliant stock transactions, assess its ethical impact, and propose regulatory measures to curb detrimental speculative practices. This research adopts a qualitative normative-juridical approach with supporting case analysis to examine Gharar practices in the Islamic capital market., analyzing related regulations, such as DSN-MUI Fatwa No. 80/2011 and POJK No. 15/POJK.04/2015, as well as empirical data on market volatility. The study shows that excessive Gharar contributes to price distortion and market volatility. Mitigating speculative practices requires strengthening corporate governance, information transparency, and law enforcement consistent with Sharia principles.